Plasticization of PEDOT:PSS by Common Additives for Mechanically Robust Organic Solar Cells and Wearable Sensors. (29th November 2014) - Savagatrup, Suchol; Chan, Esther; Renteria‐Garcia, Sandro M.; Printz, Adam D.; Zaretski, Aliaksandr V.; O'Connor, Timothy F.; Rodriquez, Daniel; Valle, Eduardo; Lipomi, Darren J.
<x xml:space="preserve">Abstract</x> Despite the ubiquity of poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) in applications demanding mechanical flexibility, the effect on the mechanical properties of common additives—i.e., dimethylsulfoxide (DMSO), Zonyl fluorosurfactant (Zonyl), and poly(ethyleneimine) (PEI)—has not been reported. This paper describes these effects and uses plasticized films in solar cells and mechanical sensors for the detection of human motion. The tensile moduli of films spin‐coated from solutions containing 0%, 5%, and 10% DMSO and 0.1%, 1%, and 10% Zonyl (nine samples total) are measured using the buckling technique, and the ductility is inferred from measurements of the strain at which cracks form on elastic substrates. Elasticity and ductility are maximized in films deposited from solutions containing 5% DMSO and 10% Zonyl, but the conductivity is greatest for samples containing 0.1% Zonyl. These experiments reveal enlargement of presumably PEDOT‐rich grains, visible by atomic force microscopy, when the amount of DMSO is increased from 0% to 5%. PEI—which is used to lower the work function of PEDOT:PSS—has a detrimental effect on the mechanical properties of the PEDOT:PSS/PEI bilayer films. Wearable electronic sensors employing PEDOT:PSS films containing 5% DMSO and 10% Zonyl are fabricated, which exhibit detectable responses at 20% strain and high mechanical robustness through elastic deformation.